Fabrication of PtNi and PtV near-surface alloys as improved catalysts for proton exchange membrane hydrogen fuel cells - Leary, Clinton Derek (Centre for Materials Engineering, 2017)
This study concerns the characterization of platinum nickel (PtNi) and platinum vanadium (PtV) near-surface alloys (NSAs) for use as improved catalysts in proton exchange membrane hydrogen fuel cells. The need for this study arose in order to further understand the principles behind the predicted catalytic properties of NSAs, to fabricate them and to characterize them experimentally. Two groups of NSAs were fabricated, namely PtNi and PtV. Pt was used as the parent metal while Ni and V were used as the solute/near surface constituents. Within these groups of pt with Ni or V, variations in coating thickness and heat treatments were used to attempt to fabricate the NSA structure. Surface profile analysis was carried out using profilometry and light microscopy. These techniques showed that surfaces were not always of a 100% mirror finish and that deposited coatings were not stable and were prone to peeling especially with coatings of greater than one layer. Elemental analysis was performed by employing energydispersive x-ray spectroscopy (SEM-EDS), proton induced x-ray emission (PIXE) and Rutherford backscattering spectrometry (RBS). These techniques helped verify the presence of the thin deposited coatings whilst also highlighting the presence of contaminants in the form of iron, manganese and chromium. Tafel Plot analysis was used to gather electrochemical data for the NSAs. In this regard, the hydrogen reduction (evolution) reaction was analyzed with the exchange current density extracted experimentally therefrom. This technique confirmed that Pt is indeed a superior catalyst, especially compared to pure Ni and V. It showed that ebeam deposition did not create coated systems which were suitable for Tafel analysis. It also illustrated that deaeration via nitrogen gas was not always effective with trace oxygen sometimes being present in the purge gas, resulting in contaminant oxygen reduction distorting the electrochemical results. Ultimately, electron-beam deposition proved to be inefficient in fabricating stable coatings for catalysis, with the coatings possibly not being adequately thin to mimic the NSA structure. This, coupled with trace oxygen reduction, prevented effective analysis of NSA catalytic properties.